APORTACIONES AL MUESTREO SUCESIVO: ESTIMADOR COMBINADO DE LA RAZÓN POBLACIONAL TIPO RAZÓN-PRODUCTO - García Luengo, Amelia V.; Artés Rodríguez, Eva M. (Revista Colombiana de Estadística, 2002)
The problem of estimation of the population ratio for the current occasion based on the samples selected over two occasions has been considered. This estimator is obtained suitably combining two independent estimates of the population ratio. The expression for optimum estimator, his variance, the optimum matched proportion, the gain in efficiency have been computed. An empirical study is made to study the performance of the proposed strategy.